Somatotropic Axis Regulation Unravels the Differential Effects of Nutritional and Environmental Factors in Growth Performance of Marine Farmed Fishes - Pérez-Sánchez, Jaume; Simó-Mirabet, Paula; Naya-Català, Fernando; Martos-Sitcha, Juan Antonio; Perera, Erick; Bermejo-Nogales, Azucena; Benedito-Palos, Laura; Calduch-Giner, Josep Alvar (Frontiers in Endocrinology, 2018)
The Gh/Prl/Sl family has evolved differentially through evolution, varying the relationship between somatotropic axis and growth rates within and across fish species. This is due to a wide-range of endogenous and exogenous factors that make variable this association along season and life cycle. However, circulating Gh and Igf-i are reliable growth markers over precisely defined groups of fishes, being proven their close association with growth in farmed gilthead sea bream with signs of deficiencies in both macro- or micro-nutrients. These findings, among others, have revitalized the use of Gh and Igf-i as key performance indicators of growth, aerobic scope and nutritional condition in marine fishes, acting sirtuins (NAD+ enzyme-deacetylases) as links between energy availability and the growth-endocrine system. At a closer look, hepatic transcripts of igf-i and gh receptors mirror changes in plasma Gh and Igf-i levels, though the relative ghr-i/ghr-ii expression ratio remains mostly unaltered over season. However, this expression ratio is highly regulated at the nutritional level, and highly-enriched plant-based diets or semi-purified diets formulated for specific nutrient deficiencies down-regulate the expression of hepatic ghr-i, decreasing the ghr-i/ghr-ii ratio. The same trend, due to ghr-ii increase, is found in white skeletal muscle, whereas impaired growth during overwintering is related to the increase of ghr-i/ghr-ii and igf-ii/igf-i expression ratios in liver and skeletal muscle, respectively. Overall, the expression of insulin receptors and igf receptors is less regulated, though the resulting expression quotient is especially high in the liver and muscle of gilthead sea bream. The nutritional and environmental regulation of the full Igf binding protein 1-6 repertoire with paralog pairs for Igfbp -1, -2, -3 -5 and -6 remains to be completed. However, tissue-specific expression profiling highlights an enhanced and nutritionally-regulated expression of igfbp-1/-2/-4 clade in liver, whereas the igfbp-3/-5/-6 clade is clearly overexpressed and regulated in skeletal muscle. Somatotropic axis is, thereby, highly informative of a wide-range of growth-disturbing and stressful stimuli, and multivariate analysis supports its use as a reliable toolset for the assessment of growth potentiality and nutrient deficiencies and requirements, especially when used in combination with selected panels of other nutritionally-regulated metabolic biomarkers.